Harnessing generative AI to boost active retrieval and retention in MOOCs with spaced repetition - Younes-Aziz Bachiri; Hicham Mouncif; Belaid Bouikhalene (Knowledge Management & E-Learning: An International Journal)
This study explores the use of artificial intelligence to improve active retrieval and retention in Massive Open Online Courses (MOOCs). We developed an AI-driven system that generates learning cards to facilitate active recall and utilize spaced repetition. The system was tested with a group of students and instructors, and the results showed significant improvements in memory retention and overall satisfaction. Expert reviews and participant feedback highlighted the system’s effectiveness in producing accurate and relevant learning cards. Despite promising outcomes, challenges with personalization and language complexity were identified, which will be addressed in future work. This research underscores the potential of AI-driven tools to enhance online learning, offering scalable and personalized solutions that can improve educational outcomes and engagement in MOOCs.